INTEGRASI SISTEM ACCOUNT PAYABLE, RECEIVING, STORE, DAN PURCHASING DALAM MENINGKATKAN EFISIENSI KEUANGAN HOTEL MERCURE IBIS SAMARINDA - Boby Gunarso; Ummi Nadroh (Jurnal Salome : Multidisipliner Keilmuan, 2025)
In the competitive hospitality industry, financial efficiency is crucial for operational sustainability and stability. This study aims to analyse the implementation of system integration between the Accounts Payable (AP), Receiving, Store, and Purchasing departments in improving financial efficiency at Mercure Ibis Samarinda Hotel. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, participatory observation, and documentation studies of employees in the hotel's four main departments. Data analysis was conducted using the Miles and Huberman interactive model, through the stages of data reduction, data presentation, and conclusion drawing. The results show that the integration of interdepartmental systems has successfully increased work efficiency by up to 50%, strengthened internal control, and improved the accuracy and transparency of financial reports. In addition, the integrated system also facilitates the audit process, speeds up managerial decision-making, and reduces the risk of administrative errors. This study concludes that the integration of the AP, Receiving, Store, and Purchasing systems has a positive impact on the financial efficiency and operational effectiveness of hotels. The successful implementation of the system is highly dependent on management support and human resource readiness. Thus, the results of this study are expected to serve as a reference for the hospitality industry in optimising digital technology-based financial management